2008
DOI: 10.1161/circresaha.108.178517
|View full text |Cite
|
Sign up to set email alerts
|

Bestrophin-3 (Vitelliform Macular Dystrophy 2–Like 3 Protein) Is Essential for the cGMP-Dependent Calcium-Activated Chloride Conductance in Vascular Smooth Muscle Cells

Abstract: Abstract-Although the biophysical fingerprints (ion selectivity, voltage-dependence, kinetics, etc) of Ca 2ϩ -activated Cl Ϫ currents are well established, their molecular identity is still controversial. Several molecular candidates have been suggested; however, none of them has been fully accepted. We have recently characterized a cGMP-dependent Ca 2ϩ -activated Cl Ϫ current with unique characteristics in smooth muscle cells. This novel current has been shown to coexist with a "classic" (cGMP-independent) Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
113
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 34 publications
5
113
0
1
Order By: Relevance
“…This study of mBest3 expression and cellular location in cardiac myocytes, together with biophysical properties as a calcium-dependent chloride channel, may provide clues to its function. A recent study by Matchkov et al (25) assigned a role for Best3 as a cGMP-dependent Ca 2ϩ -sensitive Cl Ϫ current with unique characteristics in certain smooth muscle cells. To propose a similar physiological role for Best3 in the heart is difficult because a cGMP-dependent, Ca 2ϩ -sensitive Cl Ϫ conductance has not been reported in this tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This study of mBest3 expression and cellular location in cardiac myocytes, together with biophysical properties as a calcium-dependent chloride channel, may provide clues to its function. A recent study by Matchkov et al (25) assigned a role for Best3 as a cGMP-dependent Ca 2ϩ -sensitive Cl Ϫ current with unique characteristics in certain smooth muscle cells. To propose a similar physiological role for Best3 in the heart is difficult because a cGMP-dependent, Ca 2ϩ -sensitive Cl Ϫ conductance has not been reported in this tissue.…”
Section: Discussionmentioning
confidence: 99%
“…2004, 2005), which possibly depends on bestrophins (Matchkov et al . 2008; Bulley & Jaggar, 2014). Several excellent recent reviews discuss the roles and regulation of CaCCs in smooth muscles (Sanders et al .…”
Section: Coupling Of Ano1 To Localized Ca2+ Sources In Smooth Musclesmentioning
confidence: 99%
“…In this issue of Circulation Research, Matchkov et al present compelling evidence that best-3 expression is essential for the generation of calcium-sensitive cGMP-dependent chloride channels in rat mesenteric artery. 1 Chloride channels are enigmatic beasts. Numerous phenotypes exist, as determined by their mode of activation, channel kinetics, and pore properties, but the molecular identity has only really been identified for the voltagedependent Cl Ϫ channels (CLCs) and the cAMP-dependent, cystic fibrosis transmembrane regulator (CFTR) channels.…”
mentioning
confidence: 99%
“…3 In this issue of Circulation Research, Matchkov et al suggest that we can add 1 more Cl Ϫ current to the list of identified species. 1 Perversely, the calcium-sensitive cGMP-dependent Cl current, which is the focus of the work by Matchkov et al, is among the newest additions to the Cl Ϫ current family. This article completes a body of work by this group that begins and ends with Circulation Research.…”
mentioning
confidence: 99%
See 1 more Smart Citation